Burden and management of obstetric fistula in South-East Asian region countries: A systematic review and meta-analysis - Sutapa Bandyopadhyay Neogi; Himanshu Negandhi; Priyanka Bharti; Sanjay Zodpey; Arvind Mathur (Wolters Kluwer Medknow Publications, 2020)
Background: Each year, between 50,000 and 100,000 women worldwide develop obstetric fistulae. Approximately 2 million girls across Asia and Africa are estimated to be affected by this condition. However, there is no reliable data on its prevalence in South-East Asia region (SEAR). Objectives: The objective of this study is to systematically review and synthesize the data on the prevalence and management of obstetric fistula in SEAR. Methods: We searched for the literature that described the prevalence and management practices of obstetric fistula in SEAR. We followed the PRISMA guidelines to select the articles for the review. The quality and relevance were assessed by two reviewers independently using the SIGN checklist. A total of five articles and reports were selected for the review. To review the management practices, we found 63 original studies that were included in the review. Results: We found five community-based studies estimating the prevalence of obstetric fistula in SEAR; 3 studies were from India, one from Bangladesh and one from Nepal. The pooled prevalence according to self-reports was 1.11 (3 studies including 671,133 participants, 95% confidence interval [CI] 1.09, 1.14) per 100 women. The pooled prevalence of obstetric fistula based on the clinical examination was 0.10 (3 studies involving 4547 participants, 95% CI 0.01, 0.20) per 100 women. The value was close to the pooled estimate based on the smaller studies. Conclusion: More studies are needed to estimate reliable community-based prevalence data and also need to develop evidence-based management guidelines.